Mucosal Vaccination Against SARS-CoV-2 Using Human Probiotic Bacillus subtilis Spores as an Adjuvant Induces Potent Systemic and Mucosal Immunity - Raul Ramos Pupo; Laura M. Reyes Diaz; Gisela M. Suarez Formigo; Yusnaby Borrego Gonzalez; Miriam Lastre Gonzalez; Danay Saavedra Hernandez; Tania Crombet Ramos; Belinda Sanchez Ramirez; Roberto Grau; Niels Hellings; Piet Stinissen; Oliver Perez; et al. (Vaccines, 2025)
Background/Objectives: The ongoing evolution of SARS-CoV-2 has highlighted the limitations of parenteral vaccines in preventing viral transmission, largely due to their failure to elicit robust mucosal immunity. Methods: Here, we evaluated an intranasal (IN) vaccine formulation consisting of recombinant receptor-binding domain (RBD) adsorbed onto human probiotic Bacillus subtilis DG101 spores. Results: In BALB/c mice, IN spore-RBD immunization induced strong systemic and mucosal humoral responses, including elevated specific IgG, IgM, and IgA levels in serum, bronchoalveolar lavage fluid (BALF), nasal-associated lymphoid tissue (NALT), and saliva. It further promoted mucosal B cell and T cell memory, along with a Th1/Tc1-skewed T cell response, characterized by increased IFN-γ-expressing CD4+ and CD8+ T cells in the lungs. Conclusions: All in all, these findings highlight the potential of intranasal vaccines adjuvanted with probiotic B. subtilis spores in inducing sterilizing immunity and limiting SARS-CoV-2 transmission.